농산물 표준 운송규격 제정방안 연구 - 조명기 (한국농촌경제연구원, 2005)
The agricultural market in Korea has coped with more opened environment due to the settlement of DDA and FTA bargaining agreement. Also, the issue of logistic efficiency in the sector of agricultural products' distribution from farm to retail outlet is also needed to be reviewed for the better market performance. Further, the total amount of logistic expense associated with shipment of agricultural products has been on the track of increasing trend due to the following reasons: small packing volume, non-standardized packing tools and method, manual packing process, information deficiency of retail market trend, and so on. As the tools of shipping & handling cost reduction, the enhancement of packing and piling up efficiency of agricultural products on the truck would also be important. For the improved cost efficiency of piling up agricultural products, the unused space in the luggage zone of transportation vehicle should be minimized via standardization of packing box size and specification of pallet plate. We performed the spot field-research linked to the issues of better off standardized size of packing box and shipping pallet based on numerous type of luggage zone of shipping trucks. Further, we tried to contrive new standardized rules and guide of packing & loading specification on the whole process of agricultural products' logistic flow. The focus of our project would be the enhancement of logistic flow and the minimization of shipping & handling cost when handling numerous types of agricultural products from farm to retail outlet. Mentioning about the research process, first, we contrived new logistic flow system. Second, packaged and processed agricultural products would be more recommended via the rule and regulations: Standardized Formation of Logistic & Packing System. It will induce the better efficiency of logistic system: overall cost reduction of agricultural products' shipping and handling. Finally, the newly contrived methods will renovate the current logistic infra structure of agricultural products, we wish. As initial pilot project, we performed a test and evaluation of the transportation efficiency with vegetable with ten items (radish, chinese cabbage, cabbage, potato, sweat potato, carrot, gallic, onion, water mellon, yellow melon) and fruit with five items (apple, pear, peach, hard type sweet persimmon, tangerine). We put the main focus on identifying the efficiency of transportation while considering the mentioned items' chief production regions. In the near future, the standardized logistic & packing system will be more important. Thus, we has investigated the current problems and issues associated with logistic system of agricultural products. Also, alternative implanted methods and tools with government special aid program are provided for the better off cost efficiency.